Unpacking the role of digital trust and innovation in sustaining peer-to-peer business continuity is essential for modern business operations - Amrulloh, Amri; Dwi Wibawa, Koerniawan; Sugiharto (Journal Economic Business Innovation, 2025)
Purpose: The objective of this study is to examine the impact of customer sentiment, digital trust, and service innovation on business continuity. The study will examine how operational flexibility serves as a moderating variable for peer-to-peer accommodation hosts in Indonesia.Method: A quantitative approach was employed, yielding 300 valid responses from active short-term rental hosts in Bali, Yogyakarta, and Bandung. Structural equation modeling (SEM) in SmartPLS was used to examine the direct and moderating effects.Findings: There are statistically significant positive relationships between customer sentiment, digital trust, service innovation, and business continuity. Additionally, operational flexibility significantly moderates the two relationships, amplifying the effect of the driving factors.Novelty: This study incorporates digital trust and service innovation as mediators and operational flexibility as a moderator to provide a comprehensive model for understanding the sustainability of the peer-to-peer accommodation business in the post-pandemic digital era.Implications: The results have important implications for digital platform managers and policymakers regarding strengthening platform trust, stimulating innovation, and creating flexibility to ensure the long-term sustainability of peer-to-peer firms.